A Review on – Pemphigus Vulgaris: Unnecessary ImmunityA Review on – Pemphigus Vulgaris: Unnecessary Immunity - Choudhary, Naveen (International Journal of Pharmaceutical & Biological Archive, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Pemphigus is derived from the Greek word pemphix meaning bubble or blister. Pemphigus describes a group of chronic bullous diseases, originally named by Wichman in 1791. Pemphigus vulgaris is an autoimmune, intraepithelial, blistering disease affecting the skin and mucous membranes and is mediated by circulating autoantibodies directed against keratinocyte cell surfaces Blisters in pemphigus vulgaris are associated with the binding of IgG autoantibodies to keratinocyte cell surface molecules. These intercellular or pemphigus vulgaris antibodies bind to keratinocyte desmosomes and to desmosome-free areas of the keratinocyte cell membrane. The binding of autoantibodies results in a loss of cell-to-cell adhesion, a process termed acantholysis. The antibody alone is capable of causing blistering without complement or inflammatory cells. pemphigus vulgaris is estimated at 1.6 cases per 100,000 population. Pemphigus vulgaris is a potentially life-threatening autoimmune mucocutaneous disease with a mortality rate of approximately 5-15%. The aim of treatment in pemphigus vulgaris is the same as in other autoimmune bullous diseases which is to decrease blister formation, promote healing of blisters and erosions. Corticosteroids have improved overall mortality, but now much of the mortality and morbidity in these patients relates to the adverse effects of therapy. Immunosuppressive drugs are steroid sparing and should be considered early in the course of the disease